Posttraumatic Stress Disorder Does Not Compromise Behavioral Pain Treatment: Secondary Analysis of a Randomized Clinical Trial Among Veterans - R. Jay Schulz-Heik PhD; Timothy J. Avery PsyD; Booil Jo PhD; Louise Mahoney MS, C-IAYT; Peter J. Bayley PhD (SAGE Publishing, 2022)
Background Individuals with posttraumatic stress disorder ( PTSD) and chronic pain evince different presentations, coping strategies, and treatment utilization patterns than individuals with chronic pain alone. Theorists have suggested that comorbid PTSD may complicate chronic pain treatment, and that integrated pain and PTSD treatment may be preferable to pain treatment alone. Objective Assess whether comorbid PTSD moderates Veterans' response to yoga and/or cognitive behavioral therapy (CBT) for pain. Methods Veterans with Gulf War illness (n = 75) were assessed using the Brief Pain Inventory at baseline and posttreatment as part of a randomized clinical trial. PTSD status was abstracted from participants' medical records. Results PTSD+ participants (n = 41) reported more pain at baseline than PTSD− participants (n = 34; d = .66, p < .01). PTSD+ participants experienced more improvement in pain from baseline to posttreatment than PTSD− participants by a small to moderate, marginally statistically significant amount ( d = .39, p = .07). The relationship between PTSD and treatment outcome was not moderated by treatment type (yoga vs CBT; p = .99). Observation of treatment responses across PTSD status (+ vs −) and treatment (yoga vs CBT) revealed that PTSD+ participants responded well to yoga. Conclusion PTSD is not associated with reduced effectiveness of behavioral chronic pain treatment among Veterans with Gulf War illness. Therefore behavioral pain treatment should be made readily available to Veterans with pain and PTSD. Yoga deserves further consideration as a treatment for pain among individuals with PTSD.